(untitled) (Bangladesh Journal of Medical Education, 2024)
Background: Motivation is the most essential influencing factor in academic performance. It plays an important role in academics, through its persistence and involvement which correlates with different academic dimensions and achievements. Motivational processes influence an individual’s acquisition, transfer, and use of knowledge and skills. Educationally relevant concept of motivation is yet to be revealed. High intrinsic and extrinsic motivation scores are associated with higher academic achievement; whereas low intrinsic and extrinsic motivations are associated with low academic achievement. Aim: To determine students’ academic motivational factors and its relationship with professional result. Method: A descriptive cross-sectional quantitative study conducted from January 2022 to December 2022 over 540 students; among the students 209, 119, 101 and 111 were from first, second, third and fourth phases of MBBS course respectively. A self-administered semi structured questionnaire was used for quantitative data collection. For statistical analysis chi squared tests were applied. Result: Important motivational factor for the learning was to become a good doctor (80.00%) and then to pass in the examination (65.40%). Most of the students were motivated by combined intrinsic and extrinsic mode of motivation; but these findings had no association with the performance of professional examinations. Conclusion: This study has found that academic motivation of medical students could be influence by different factors. The existence of correlations between academic motivation and professional performance is still questionable and nonconclusive. BJME, Volume-15, Issue-01, January 2024: 67-74